Distalization of maxillary arch and correction of Class II with mini-implants: A report of two cases - Pawankumar Dnyandeo Tekale; Ketan K Vakil; Jeegar K Vakil; Ketan A Gore (Wolters Kluwer Medknow Publications, 2015)
This article reports the successful use of mini-screws in the maxilla to treat two patients of age 21-year and 17-year-old girls. Both the patients had a skeletal Class II malocclusion with protrusive maxillary teeth and angels Class II mal-occlusion. Temporary anchorage devices (TADs) in the posterior dental region between maxillary second premolar and maxillary first molar teeth on both sides were used as anchorage for the retraction and intrusion of her maxillary anterior teeth. Those appliances, combined with a compensatory curved maxillary archwire, eliminated spacing, deep bite, forwardly placed and proclined upper front teeth and the protrusive profile, corrected the molar relationship from Class II to Class I. With no extra TADs in the anterior region for intrusion, the treatment was workable and simple. The patient received a satisfactory occlusion and an attractive smile. This technique requires minimal compliance and is particularly useful for correcting Class II patients with protrusive maxillary front teeth and dental deep bite.